Prognosis of patients in prolonged coma after severe carbon monoxide poisoning. (August 2021) - Gao, Y; Gu, H; Yang, J; Yang, L; Li, Z; Zhang, J
Background: Late recovery in patients following prolonged coma from carbon monoxide poisoning have been reported, but the probability is unclear. The purpose of this research was to assess the prognosis of patients in prolonged coma after severe carbon monoxide poisoning and related clinical and imaging features. Methods: There were 13 patients who had been in a state of coma for >7 days after acute carbon monoxide poisoning in the retrospective observational study, and demographic data, clinical data, laboratory data, complications, and image data were collected. Outcome was assessed by means of the Glasgow outcome scale after 1 year. The relationship between complications and imaging manifestations and prognosis was also analyzed. Results: One year after severe carbon monoxide poisoning, two patients (15.4%) had died (GOS 1), nine (69.2%) were in a persistent vegetative state (GOS 2), one (7.7%) was moderately disabled (GOS 4), and one (7.7%) achieved a good recovery (GOS 5) with minimal disability. Conclusions: Most patients with prolonged coma after severe carbon monoxide poisoning had a poor prognosis, although the younger patients had a better prognosis. Respiratory failure, hypotension and renal failure during the course of the disease were associated with a poor prognosis. The prognosis of patients with injuries in two sites in early CT was poor. Multiple lesions (≥3) and extensive white matter damage (Fazekas grade (PVH or DWMH) = 3) on MRI of chronic phase were also associated with a poor prognosis.